A novel method to evaluate the thermal shock behavior of ZrB2-SiC-graphite composites under alternating complex thermal stress environments. Issue 14 (1st November 2016) - Jin, Hua; Meng, Songhe; Xu, Chenghai; Niu, Jiahong; Xie, Weihua
Abstract: The thermal shock behavior of ZrB2 -SiC-graphite (ZSG) composites was investigated in this study using a novel method of simulating complex thermal stress states that involved electric resistance heating followed by dynamic water cooling. The ZSG composites were heated and cooled to 1020–2020 °C at a constant heating rate of 134 °C/s and a constant cooling rate of 536 °C/s. The residual strength of the composites decreased at temperature difference of 1000–1400 °C. This weakening in strength was attributed to the multiple microcracks and flaws that were created by the two-dimensional thermal stresses and by the expanding and shrinking in the volume of the composites, attributed to chemical/physical reactions. Next, it was found that the residual strength of the composites increased at temperature difference of 1400–1700 °C, due to the formation of a liquid SiO2 glass and the increase in the quantity of oxides both of which were favorable to healing the flaws and cracks. Finally, the residual strength decreased slowly at temperature difference above 1700 °C, which was attributed to the ZrO2 -induced crack healing. It was found that the thermal shock behavior of the ZSG composites depended on both the temperature difference and the mode of the thermal shock loading. The material was particular sensitivity to the regime of alternating heating and cooling, which would be similar to actual flight conditions.